2021
DOI: 10.21203/rs.3.rs-753320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unity in Diversity - Food Plants and Fungi of Sakartvelo (Republic of Georgia), Caucasus

Abstract: Background: The Republic of Georgia is part of the Caucasus biodiversity hotspot, and human agricultural plant use dates bat at least 6000 years. Over the last years lots of ethnobotanical research on the area has been published. In this paper we analyze the use of food plants in the 80% of Georgia not occupied by Russian forces. We hypothesized that, (1) given the long tradition of plant use, and the isolation under Soviet rule, plant use both based on home gardens and wild harvesting would be more pronounced… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is worth noting the PCA results validate the descriptive results. Although important inferences can be made using descriptive statistics, analysing ethnobotanical data using dimension reduction tools such as PCA are considered to be more effective (Bussmann et al 2021;Leonti, 2022).…”
Section: Demographic Profile Of the Respondentsmentioning
confidence: 99%
“…It is worth noting the PCA results validate the descriptive results. Although important inferences can be made using descriptive statistics, analysing ethnobotanical data using dimension reduction tools such as PCA are considered to be more effective (Bussmann et al 2021;Leonti, 2022).…”
Section: Demographic Profile Of the Respondentsmentioning
confidence: 99%
“…We also compared our ethnomedicinal data with data previously gathered from the Balkans to the Caucasus, as we did for our data and previous findings in northern Anatolia ( Ivancheva and Stantcheva, 2000 ; Koleva et al, 2015 ; Bussmann et al, 2016a ; Bussmann et al, 2016b ; Bussmann et al, 2017a ; Bussmann et al, 2017b ; Jakeli et al, 2018 ; Bussmann et al, 2020a ; Bussmann et al, 2020b ; Kazanci et al, 2020 ; Kazanci et al, 2021 ). It was shown that nineteen taxa had similar uses to those in our study: Plantago major subsp.…”
Section: Discussionmentioning
confidence: 96%
“…2006; http://www.ethnobiology.net/what-we-do/coreprograms/ise-ethics-program/code-of-ethics/code-in-english/) and the protocol was approved by the Ethics Committee of the National University of Trujillo (code N°: PR003P-2022/CEIFYB). A standard questionnaire was applied through structured semi-open interviews in which the plants used to treat some viral diseases were inquired about, taking into account the vernacular name, uses and traditional medicinal properties, forms, and uses of preparation, dose, and administration of the plant used [86,87].…”
Section: Ethnobotanical Studymentioning
confidence: 99%